The Effect of Using Constructive (PDEODE) Strategy in Developing Some Science Process Skills "A Field Study among Basic Education Schools in Tartous City" - محمد, صبا (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
This study aimed to identify the effect of using the constructive (PDEODE) strategy in developing some science process skills (observation, classification, prediction, deduction, data interpretation, and hypothesis formulation) in Science for basic fifth-grade students among schools in Tartous city. To achieve the aims of this study, the semi-experimental method was used, and a sample of fifth-grade students from basic education schools at Tartous City was selected, consisting of (70) students, distributed equally in two groups: an experimental group learned according to constructive (PDEODE) strategy, and a control group learned according to the usual method. The test of science process skills (prepared by the researcher) was applied during the research, after ascertaining its sincerity and stability. The results showed that the constructive (PDEODE) strategy has a significant positive effect in developing some science process skills for the basic fifth-grade students, and it was suggested that attention should be paid to train teachers to use the (PDEODE) strategy in the process of teaching, conducting pre-service and in-service training courses, and investigating the effect of the (PDEODE) strategy in overcoming the difficulties of learning Science among students with learning difficulties, in addition to study the relationship between students’ attitudes toward learning Science, and their level of the science process skills.